Analysis of the Current Status and Prospects of Extended Range Electric Vehicle Powertrain under the Background of Carbon Peaking and Carbon Neutrality Goals - Meng, Lingshuo (International Journal of Mechanical and Electrical Engineering, 2024)
With increasing global concern about environmental protection and climate change, the automotive industry is also under stress to reduce emissions and improve energy efficiency. In this context, extended range power technology, as a hybrid solution that integrates traditional internal combustion engine and electric drive system, has attracted much attention. At present, the extended range power technology has made some progress and has been applied in the market. By combining an internal combustion engine with a battery pack, extended-range vehicles can achieve longer driving ranges and lower exhaust emissions. In addition, in low-speed driving situations such as urban traffic, pure electric mode can play an advantage, thereby improving energy efficiency. Looking ahead, as the automotive industry moves towards carbon neutrality, extension-range power technology is expected to become one of the mainstream options. Through continuous innovation and improvement, it can be predicted that it will make more breakthroughs in energy conservation and emission reduction, improve driving experience, and eventually become one of the important engines to promote the sustainable development of the automotive industry.